Scale Insects (Coccoidea) Damaging Pear (Pyrus Communis L.) and Their Bioecological Characteristics - Teshaboyeva Maftuna Ikromjonovna (American Journal of Biology and Natural Sciences, 2026)
This article describes the species composition, bioecological characteristics, life cycle, and level of damage caused by scale insects (Coccoidea) found on pear (Pyrus communis L.) trees. Under the conditions of the Fergana Valley, species such as Parthenolecanium corni, Quadraspidiotus perniciosus, and Lepidosaphes ulmi are widely distributed. Information is provided on the phenology, population dynamics, and damage levels of these pests.